TRADISI DODADI YO BACA DI DESA TOWARA KECAMATAN MOROTAI JAYA (STUDI LIVING QUR’AN) - Piong, Jainudin; Irfan, Irfan; Arsyad, Wijayanti Hi; R, Patria; Bakar, Abu; Raisya, Nurul; Thohir, M. (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
This research aims to discuss the tradition of dodadi yo baca in towara village, morotai jaya sub-district. This research uses the living qur'an approach method. The formal object of this research is a form of respect and there are certain expectations. While the material object is the dodadi yo baca tradition. while the scope of this research is in Towara village, Morotai Jaya sub-district, Morotai Island district. The context is to find out the community's understanding of the verses recited in the dodadi yo baca tradition. The results and discussion in this study are the Implementation of the Dodadi Yo Baca Tradition begins with the delivery of food and the type of food made is yellow rice, the delivery is carried out using a type of raft that comes from grain and this offering is taken to the sea and then delivered by the Dodadi tetuah in a boat driven by several people who have been assigned, while accompanied by a tambourine blow.